Optimization of cultivation conditions for combined nutrient removal and CO2 fixation in a batch photobioreactor. Issue 5 (3rd October 2016) - Al Ketife, Ahmed MD; Judd, Simon; Znad, Hussein
Abstract: BACKGROUND: The application of Chlorella vulgaris for simultaneous CO2 biofixation and nutrient removal has been optimised using response surface methodology (RSM) based on Box Behnken design (BBD). Experimental conditions employed comprised CO2 concentrations ( Cc, g ) of 0.03–22% CO2, irradiation intensities ( I ) of 100–400 μE, temperatures of 20–30 °C and nutrient concentrations of 0–56 and 0–19 mg L −1 nitrogen and phosphorus, respectively, the response parameters being specific growth rate μ, CO2 uptake rate Rc and %nutrient removal. RESULTS: Over 10 days the biomass concentration reached almost 3 g L −1 for Cc, g of 5% CO2, with corresponding values of 0.74 g L −1 day −1 and 1.17 day −1 for Rc and μ, respectively, and 100% nutrient (N and P) removals. At 22% CO2 the Rc and μ decreased by around an order of magnitude, and nutrient removal also decreased to 79% and 50% for N and P, respectively. CONCLUSION: Optimum values 5% CO2, 100 μE and 22 °C were identified for Cc, g, I and T, respectively, with μ and Rc reaching 1.53 day −1 and 1 g L −1 day −1, respectively, along with associated nutrient removal of 100%. Regression analysis indicated a good fit between experimental and model data. © 2016 Society of Chemical Industry